Designing for inclusiveness in education projects: the case of the European University of Technology’s XR Team - McQuillan, Deirdre; Nocchi, Susanna; Gabaudan, Odette; Schalk, Ana; Nicolaou, Anna; Parmaxi, Antigoni; Hernandez, Esther (My University, 2021)
This paper will present the case of the XR project team within the European University of Technology (EUt+). The team is tasked with developing an extended reality (XR) virtual reality (VR) approach to help students and staff overcome language and cultural barriers in international mobility. The aim of the project ultimately is to enhance the experience of physical student mobility and to ensure international opportunities for students are more inclusive. As research on the problem is still in progress, the team found themselves constructing their own understanding of designing for inclusiveness in the project. This paper presents the case through a qualitative case study methodology involving reflective journals of project participants, a focus group discussion and documentary analysis connected to the project. The findings from the study show how the understanding of ‘inclusiveness’ is constructed through social interactions and consequently how designing for inclusiveness in digital projects in education is a journey influenced by evolving meanings. Our study makes important contributions to the students with disability literature and technology in education literature.
Keywords: Extended reality; Virtual reality; Language barriers; Cultural barriers